Nuclear Magnetic Resonance Aerosolomics: A Tool for Analysis of Polar Compounds in Atmospheric Aerosols - Horník, Štěpán; Sýkora, Jan; Schwarz, Jaroslav; Ždímal, Vladimír (ACS omega, 2020)
Nuclear magnetic resonance aerosolomics was proposed as a new approach to the analysis of the water-soluble organic compound fraction in aerosol particulate matter. The identification of individual compounds is based on a comparison of precise chemical shifts in the 1H NMR spectrum with the signals in the standards library. For this purpose, Chenomx metabolomics software and a comprehensive spectra library of 150 compounds known from chemistry of aerosols were used. This approach enabled the identification of 60 compounds in real aerosol samples collected at a suburban site in Prague. Using the metabolomic spectra library, three new compounds were identified in aerosols for the first time, and an association of four other compounds to the atmospheric particulate matter was confirmed. The obtained concentration profiles of all identified chemical individuals were subsequently subjected to advanced statistical analysis. NMR aerosolomics clearly differentiates between summer and winter aerosol samples via multivariate statistical analysis and revealed some interesting trends in composition, according to aerosol particle size. Furthermore, the univariate statistical analysis was applied to highlight compounds responsible for the group separation, and possible sources of these compounds were suggested.